2016
DOI: 10.1590/0001-3765201520140570
|View full text |Cite
|
Sign up to set email alerts
|

Feeding ecology of Erythrolamprus jaegeri jaegeri (Günter, 1858) and Erythrolamprus poecilogyrus sublineatus (Cope, 1860) in the coastal zone of Subtropical Brazil (Serpentes, Dipsadidae)

Abstract: The snakes Erythrolamprus jaegeri jaegeri and Erythrolamprus poecilogyrus sublineatus are sympatric and syntopic in the coastal region of southern Brazil. Herein, we analyzed the diet composition to evaluate the niche breadth and the prey selection by both species. We examined 192 specimens, and analysis of stomach contents revealed that both species predominantly consume anurans. However, the diet of E. j. jaegeri consists mainly of fi sh and amphibians, whereas that of E. p. sublineatus is broader, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…Erythrolamprus poecilogyrus sublineatus (Cope, 1860) is one of the most abundant Dipsadidae species found in the coastal plain of Rio Grande do Sul, Brazil (Correa et al, 2016). This species occurs in a variety of habitats, including wetlands, fields, forest and dunes formations, besides of urbanized areas and patches of eucalyptus.…”
Section: Introductionmentioning
confidence: 99%
“…Erythrolamprus poecilogyrus sublineatus (Cope, 1860) is one of the most abundant Dipsadidae species found in the coastal plain of Rio Grande do Sul, Brazil (Correa et al, 2016). This species occurs in a variety of habitats, including wetlands, fields, forest and dunes formations, besides of urbanized areas and patches of eucalyptus.…”
Section: Introductionmentioning
confidence: 99%
“…The altitudinal range is narrower in comparison with the nominal subspecies (1200–1850 m asl). In the animal world, differences in dietary ecology may be exhibited among subspecies (e.g., [ 59 , 60 ]) or populations (e.g., [ 61 ]). Considering that the Golden Alpine salamander occurs in a different ecological context in comparison to the other Alpine salamander subspecies, its diet could reflect this ecological uniqueness in terms of diversity and abundance of consumed prey.…”
Section: Discussionmentioning
confidence: 99%
“…Details about the capture of this snake are unknown, but after examining the material carefully we were unable to identify any signs that the specimen had been mistreated. Populations of E. poecilogyrus and L. macrosternum are common in the Trinidad region (Rivas et al 2022) and on the Benian Floodplains (Eversole et al 2021); therefore, predator-prey interactions between these two species are likely, and the relationship has been recorded in Argentina (Prieto et al 2012), as has that of E. poecilogyrus and L. latrans in Rio Grande do Sul, Brazil (Corrêa et al 2016). The most frequent amphibian prey of E. poecilogyrus registered by Prieto et al (2012) in the wetlands of northern Argentina were bufonids, leptodactylids, and hylids in that order.…”
Section: T a B L E O F C O N T E N T S F E A T U R E A R T I C L E Smentioning
confidence: 99%
“…Erythrolamprus poecilogyrus is active during both day and night, and is most frequently documented during the rainy season (Marqués et al 2001;Sawaya et al 2008;Rivas et al 2022). It is a typically terrestrial generalist found in grasslands, forests, caves, cracks, curiches (wetlands), disturbed areas, and even houses (Marqués et al 2001;Sawaya et al 2008;Palmuti et al 2009;Prieto et al 2012;Corrêa et al 2016;Rivas et al 2022). It feeds on fishes, amphibians, reptiles, and mammals; however, its main diet consists of anurans, including eggs and tadpoles (Pinto and Fernandes 2004;Prieto et al 2012;Alencar and Nascimento 2014;Azarak and Farias 2017;Cabral et al 2017;Andrade et al 2020;Oliveira et al 2021;Rivas et al 2022), with leptodactylids accounting for about 30% of documented anuran prey (Corrêa et al 2016).…”
mentioning
confidence: 99%